Relationship between corporate social performance and corporate financial performance as mediated by firm size in the banking industry in Bandung, Indonesia - Herman, Ivone (Animo Repository, 2005)
Numerous studies have been done to investigate the relationship between Corporate Social Performance (CSP) and Corporate Financial Performance (CFP) but until now, no clear empirical relationship has been established. Various theoretical arguments have been developed by the researchers however research findings show that the relationship between CSP and CFP is still vague. No universally-accepted relationship exits. The most significant one is that the biggest number of the studies showed positive relationship between CSP and CFP. Various arguments have been made regarding the relationship between firm's social responsibility and their financial performance. Some researchers suggested that a firm size has effect to CSP and CFP. In contrast, other have argued that it does not affect CSP and CFP. This study will initially attempt to investigate if any, the effect of firm size to CSP and CFP. Furthermore, the relationship of CSP and CFP will also be analyzed. The data will come from a sample of banks from the banking industry in Banding, Indonesia. The size of these firms will be based on their annual revenue or income and total assets of the firms will be based on their annual revenue of income and total assets of the firm whereas financial performance will be based on Return on Assets, Return on Equity and level of profitability. On the other hand, the CSP will be measured based on the bank's corporate responsiveness and policy for year 2004, given the following criteria: community relations, employee relations, supplier relations and customer relations. These four dimensions are selected based on stakeholder theory perspective. Four of those rated attributes emphasize key stakeholder relations that might be included among those emphasized as important emerging influences on corporate strategy. The study found that there is no significant relationship between CSP and CFP. The fact that the strong association between firm size and CSP is statistically significant, given the small sample size, is both surprising and confirms previous studies which have also found such relationship. The study failed to find a strong relationship between CFP and firm size. In terms of firms size as a mediating variable for relationship between CSP and CFP, the study has failed to garner empirical support. On the other hand, the study has garnered empirical support for the relationship between CSP and CFP with size as moderating variable since there is a difference of degree and significance of CSP-CFP relationship between small and large banking firms.